Association of Midlife Plasma Amyloid-β Levels With Cognitive Impairment in Late Life: The ARIC Neurocognitive Study. (14th September 2021) - Sullivan, Kevin J.; Blackshear, Chad; Simino, Jeannette; Tin, Adrienne; Walker, Keenan A.; Sharrett, A. Richey; Younkin, Steven; Gottesman, Rebecca F.; Mielke, Michelle M.; Knopman, David; Windham, B. Gwen; Griswold, Michael E.; et al.
Abstract : Background and Objectives: To evaluate the association between midlife plasma amyloid-β (Aβ1-42, Aβ1-40, Aβ42 :Aβ40 ) and risk of mild cognitive impairment (MCI) and dementia. Methods: Plasma Aβ42 and Aβ40 were retrospectively measured with a fluorometric bead-based immunoassay in a subsample of the Atherosclerosis Risk in Communities cohort study. We investigated the relationship of plasma Aβ42, Aβ40, and Aβ42 :Aβ40 ratio measured in midlife and late life and the change from midlife to late life to risk of MCI, dementia, and combined MCI/dementia outcomes in late life (from 2011–2019). We used multinomial logistic regressions estimating relative risk ratios (RRRs) of these cognitive outcomes vs cognitively normal adjusted for age, sex, education, site-race, APOE, hypertension, diabetes, and body mass index. Results: A total of 2, 284 participants were included (midlife mean age 59.2 ± 5.2, 57% female, 22% Black). Each doubling of midlife Aβ42 :Aβ40 was associated with 37% lower risk of MCI/dementia (RRR 0.63, 95% confidence interval [CI] 0.46–0.87), but only up to approximately the median (spline model threshold 0.20). Every 1-SD increase in plasma Aβ42 (10 pg/mL) was associated with 13% lower risk of MCI/dementia (RRR 0.87, 95% CI 0.77–0.98), whereas every 1-SD increase in plasma Aβ40 (67 pg/mL) was associated with 15% higher risk of MCI/dementia (RRR 1.15, 95% CI 1.01–1.29). Associations were comparable but slightly weaker statistically when models were repeated using late-life plasma Aβ predictors. Aβ42 and Aβ40 increased from midlife to late life, but changes were not associated with cognitive outcomes. Discussion: Midlife measurement of plasma Aβ may have utility as a blood-based biomarker indicative of risk for future cognitive impairment.